The Association Between Drinking Water Management Behavior and the Level of Macronutrient Adequency with Nutritional Status of Toddlers: Hubungan Perilaku Pengelolaan Air Minum dan Tingkat Kecukupan Zat Gizi Makro dengan Status Gizi Balita - Khoirul Anwar, SGz, MSi; Lulu Indria Setyani (Amerta Nutrition, 2022)
Background: Currently, in Indonesia various types of nutritional problems still occur in toddlers such as stunting, underweight, and wasting. There are several factors that influence the occurrence of these nutritional problems, such as drinking water management behavior and nutritional intake. Objectives: To analyze the relationship between drinking water management behavior and the adequacy level of macronutrients on the nutritional status of children under five. Methods: This study used a cross-sectional design with locations in the working area of the Bantargebang Public Health Center, Bekasi City. Subjects were 96 toddlers aged 24-59 months and mothers of toddlers who were taken by purposive sampling. Data collection on body weight (BB) and height (TB) was carried out through direct measurements, data on drinking water management behavior using a questionnaire, and the adequacy level of macronutrients using the SQ-FFQ form. Statistical test using descriptive test, chi-square test and relationship test using Spearman. Results: Inappropriate drinking water management behavior is applied by 61.5% of respondents. The energy adequacy level of toddlers obtained an average of 99.8%, the adequacy level of protein was 94.4%, the adequacy level of fat was 87.3%, and the adequacy level of carbohydrates was 101.5%. As many as 18.8% of toddlers are underweight, 17.7% of toddlers are stunted, and 27.1% of toddlers are wasted. The results showed that drinking water management behavior was associated with underweight (p=0.001), stunting (p=0.026), and wasting (p<0.001). There is a relationship between the level of energy sufficiency and wasting (p=0.004). The level of protein adequacy was also associated with underweight (p<0.001) and stunting (p=0.025). The results also showed that the level of fat adequacy was associated with underweight (p=0.049). The level of carbohydrate adequacy was also found to have a relationship with wasting (p=0.006). Conclusions: Drinking water management behavior has a relationship with stunting, underweight, and wasting. There is a relationship between the level of energy adequacy and wasting; protein adequacy level with underweight and stunting; level of fat adequacy with underweight; and the level of carbohydrate sufficiency associated with wasting.